Psychometric Properties of the Persian Version of the Short Beck Depression Inventory with Iranian Psychiatric Outpatients. (17th May 2016) - Dadfar, Mahboubeh; Kalibatseva, Zornitsa
Abstract : The short form of the Beck Depression Inventory (BDI-13) is useful for the screening and assessment of depression in clinical and research settings. The aim of the present study was to investigate the psychometric properties of the Persian (Farsi) version of BDI-13 in an Iranian clinical sample. The sample consisted of 52 Iranian psychiatric outpatients who received services at psychiatric and psychological clinics at the School of Behavioral Sciences & Mental Health-Tehran Institute of Psychiatry, Iran University of Medical Sciences (IUMS) in Tehran, Iran. The study examined the reliability, construct validity, and factor structure of the instrument. The instrument indicated good reliability with Cronbach's alpha of .85 and strong construct validity based on moderate to strong positive correlations with other measures of mental health issues. Using a Principal Component Analysis and Varimax Rotation with Kaiser Normalization, three factors were identified and labeled Affective (F1), Somatic/Vegetative (F2), and Cognitive/Loss of Functioning (F3). The current factor structure suggests that depression is a multidimensional construct in an Iranian clinical sample. This study provides further evidence that the Persian version of the BDI-13 is a psychometrically sound instrument that can be used for clinical and research purposes in Iran.